Analysis of tensile mechanical characteristics of fibre reinforced backfill through splitting tensile and three-point bending tests. Issue 3 (16th March 2022) - Xue, Gaili; Yilmaz, Erol; Feng, Guorui; Cao, Shuai
ABSTRACT: The cut-and-fill mining method is used in metalliferous mines thanks to backfilling instead of ore pillars. However, the stability of the artificial cemented tailings backfill (CTB) roof is one of the key influencing factors for this method. CTB has the characteristics of poor bending resistance and strong brittleness, which is unfavourable for the preparation of artificial CTB roof. In this study, gold tailings and polypropylene fibres were used to make fibre reinforced backfill (FRB). Some splitting tensile strength and three-point bending tests were executed on laboratory-made FRB samples. The feasibility of FBR's industrial application was also assessed. The results verify that FRB's splitting tensile and bending strengths increase significantly when added fibres to the mix. This is mostly as a result of the fibre effect of inhibiting crack propagation in FRB samples. Artificial backfill roof was manufactured by using CTB and FRB samples. Besides, the thickness of fibre reinforced backfilling is 0.8 m. The unique findings from this study attest that it is reliable to use FRB material for preparing artificial CTB roof in mines. Besides, this study will hopefully contribute to the secure filling design for underground metalliferous mines and enhance the stability of backfilling structures.